The Effect of Risk Management on the Financial Performance of Insurance Companies in Indonesia - Hana Fitri Rahmadhani; Putri Nurluthfi Azzahra; Farah Margaretha Leon (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
The purpose of this study is to analyze various types of financial risks on the performance of insurance companies in Indonesia by including control variables such as leverage, age of the firm, size of the firm, and an additional variable, namely board size. The risks analyzed include credit, market, operational, liquidity, underwriting, and solvency risks. This study uses a quantitative method with secondary data from 32 conventional insurance companies for the period 2020–2024. The focus on conventional insurance was chosen because it has better data completeness, consistent reporting standards, and a significant role in the national insurance market to provide a clear picture of financial risk patterns in the industry. In addition, this sector is interesting to study because it has a complex business structure, broad risk exposure, and high sensitivity to changes in economic conditions. The analysis was conducted using panel data regression, and the fixed effects model was determined to be the most appropriate model. The novelty of this study lies in the addition of board size to assess the supervisory role in the relationship between financial risk and profitability. The results of the study show that credit risk has a positive impact on performance, while other variables such as market risk, operational risk, leverage, and age of the firm have a negative impact. Meanwhile, liquidity risk, underwriting risk, solvency risk, size of the firm, and board size do not show a significant effect, emphasizing the importance of effective risk management and operational efficiency.